Soft glass/polymer multimaterial fibre bundles for thermal imaging - Lousteau, J.; Ventura, A.; White, N.; Slimen, F. B.; Janíček, Petr; Poletti, F. (SPIE - The International Society for Optical Engineering, 2017)
A bundle consisting of 1200 fibre elements each made of chalcogenide glass and Teflon was fabricated. Accurate thermal imaging of a square heating element could be carried out through a 1.15 m long bundle section.
Svazek multimateriálních vláken z měkkého skla / polymeru pro tepelné zobrazování
Keywords: Endoscopic imaging; Thermal imaging; Fiber optics imaging; infrared fiber optics; Glass and other amorphous materials; Endoskopické zobrazování; Tepelné zobrazování; Zobrazování vláknovou optikou; infračervená optika; Sklo a jiné amorfní materiály